An examination of the relationship between childhood emotional abuse and borderline personality disorder features: The role of difficulties with emotion regulation. (January 2015) - Kuo, Janice R.; Khoury, Jennifer E.; Metcalfe, Rebecca; Fitzpatrick, Skye; Goodwill, Alasdair
Abstract: Childhood abuse has been consistently linked with borderline personality disorder (BPD) and recent studies suggest that some forms of childhood abuse might be uniquely related to both BPD and BPD features. In addition, difficulties with emotion regulation have been found to be associated with childhood abuse, BPD, as well as BPD features. The present study examined (1) whether frequency of childhood emotional abuse is uniquely associated with BPD feature severity when controlling for other forms of childhood abuse and (2) whether difficulties with emotion regulation accounts for the relationship between childhood emotional abuse and BPD feature severity. A sample of undergraduates ( n = 243) completed the Childhood Trauma Questionnaire – Short Form, Difficulties in Emotion Regulation Scale, and Borderline Symptom List-23. Multiple regression analyses and Structural Equation Modeling were conducted. Results indicated that frequency of childhood emotional abuse (and not sexual or physical abuse) was uniquely associated with BPD feature severity. In addition, while there was no direct path between childhood emotional abuse, childhood physical abuse, or childhood sexual abuse and BPD features, there was an indirect relationship between childhood emotional abuse and BPD features through difficulties with emotion regulation. These findings suggest that, of the different forms of childhood abuse, emotional abuse specifically, may have a developmental role in BPD pathology. Prevention and treatment of BPD pathology might benefit from the provision of emotion regulation strategies.